Analisis Pelanggaran Prinsip Kesantunan Dan Penggunaan Strategi Kesantunan Dalam Tindak Tutur Anjuran Pada Reality Show “Terrace House: Opening New Doors” - Getaya, Andardisha; Hapsari, Eky Kusuma; Hamdi, Muhammad Ali (Vocational College of Diponegoro University, 2024)
This study aims to examine the violations of politeness principles in recommending speech acts that occur in the reality show